Análise da performance de sistemas de comunicação sem fio baseados em OFDM utilizando um modelo de propagação na área urbana de São Paulo - SP - Almeida, Karine Souza de (2016)
By using the Orthogonal Frequency Division Multiplexing (OFDM), it is possible to transmit by a channel a more robust signal and less susceptible to interferences. When such technique, based on orthogonal subcarriers, is combined with the use of propagation models, which are relevant tools for simulating the signal behavior in respect to environmental parameters and antenna configurations, it is feasible to have an evaluation about the performance of these systems, improving their project phase. Therefore, this work presents the use of OFDM technique applied to two propagation models: a two-ray geometric model and a microcellular model adapted to the Paulista Avenue, São Paulo, SP, having as objective the analysis of a mobile communication system through Bit Error Rate (BER). In the developed application using the MAtrix LABoratory (MATLAB) software, the mobile communication system based on OFDM admits several scenarios during the simulation, so that scenarios are related to positioning of the antennas, heights, type of modulation, size of the bit sequence to be sent, and others. The adopted OFDM architecture has been the IFFT/FFT and based on it, the system performs the transmission and reception of a bit set through a channel with interference by using different digital modulations, making appropriate comparisons.